Responding to Sexual Assault: A Systematic Review of Police Training Interventions and Outcomes - McQueen, Karen (Crime & delinquency, 2025)
Sexual assault is a worldwide issue that impacts many individuals, often with serious and long-lasting effects. Police play an important role for victims seeking justice. However, police response has been highly criticized as less than optimal. One question that remains unclear is whether sexual assault training improves police response. This quantitative review examined the effect of police training on diverse police outcomes. Five databases were systematically searched, which resulted in 10 published papers reporting on 12 studies. Our review found consistent evidence that suggests that sexual assault police training can improve various police attitudes, knowledge, and behaviors. However, further research is needed before specific recommendations regarding training can be made.